Motivation, Environment, and Discipline: Impact on Employee Performance: Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan: Studi Kuantitatif - Munfarizatul Maisyuroh; Hasan Ubaidillah (Academia Open, 2023)
This study aimed to investigate the impact of work motivation, work environment, and work discipline on employee performance at a leading organization. The research utilized a quantitative approach, employing data processing in numerical form. The entire population of 52 employees was included as the sample, ensuring a saturated sample. Questionnaires were administered, and data were analyzed using the IBM SPSS version 22 program. The findings revealed that work motivation positively and significantly influenced employee performance, while the work environment also exhibited a positive and significant effect. However, work discipline showed a negative and insignificant relationship with employee performance. These results contribute to our understanding of the factors shaping employee performance and emphasize the importance of fostering a motivational work environment. Highlights: Work motivation and work environment positively impact employee performance. Work discipline does not significantly affect employee performance. This quantitative study explores the interplay between motivational factors, the work environment, and employee performance, providing insights for enhancing workplace productivity. Keywords: Work motivation, work environment, work discipline, employee performance.